P2Y14 receptor is functionally expressed in satellite glial cells and mediates interleukin‐1β and chemokine CCL2 secretion. Issue 11 (29th April 2019) - Lin, Jiu; Liu, Fei; Zhang, Yan‐yan; Song, Ning; Liu, Meng‐ke; Fang, Xin‐yi; Liao, Da‐qing; Zhou, Cheng; Wang, Hang; Shen, Jie‐fei
Abstract: Satellite glial cells (SGCs) activation in the trigeminal ganglia (TG) is critical in various abnormal orofacial sensation in nerve injury and inflammatory conditions. SGCs express several subtypes of P2 purinergic receptors contributing to the initiation and maintenance of neuropathic pain. The P2Y14 receptor, a G‐protein‐coupled receptor activated by uridine diphosphate (UDP)‐glucose and other UDP sugars, mediates various physiologic events such as immune, inflammation, and pain. However, the expression, distribution, and function of P2Y14 receptor in SGCs remains largely unexplored. Our study reported the expression and functional identification of P2Y14 receptor in SGCs. SGCs were isolated from TG of rat, and the P2Y14 receptor expression was examined using immunofluorescence technique. Cell proliferation and viability were examined via cell counting kit‐8 experiment. Immunofluorescence demonstrated the presence of P2Y14 receptor in SGCs. Immunofluorescence and western blot showed that UDP‐glucose treatment upregulated glial fibrillary acid protein, a common marker for glial activation. Extracellular UDP‐glucose enhanced the phosphorylation of extracellular signal‐regulated kinase (ERK), c‐Jun N‐terminal kinase (JNK), and p38, which were both abolished by the P2Y14 receptor inhibitor (PPTN). Furthermore, quantitative reverse transcription polymerase chain reaction and enzyme‐linked immunosorbent assay demonstrated that extracellular UDP‐glucose significantly enhanced interleukin‐1β (IL‐1β) and chemokine CCL2 (CCL2) release, which was abolished by PPTN and significantly decreased by inhibitors of MEK/ERK (U0126) and p38 (SB202190). Our findings directly proved the functional presence of P2Y14 receptor in SGCs. It was also verified that P2Y14 receptor activation was involved in activating SGCs, phosphorylating MAPKs, and promoting the secretion of IL‐1β and CCL2 via ERK and p38 pathway.